Optimizing the Use of Digital Libraries in Basic Education - Putri, Candra Avista; Syaifuddin, Ahmad; Rohman, Nurur; Aziz, Abd; Ponijan, Rizky Maulidya Putri (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The development of the times is getting faster with technology. Digital madrasas also need other supporters for better educational sustainability. In the era of digitalization, the Madrasah as an educational institution also has a role in keeping up with the times. This study aims to describe efforts to optimize digital libraries and analyze the strategy for developing digital collections in madrasah libraries. This study uses a descriptive qualitative method, with data collection techniques including observation of the condition and state of the digital library in the Madrasah, interviews with resource persons as digital library managers, and documentation of activities in the digital library. The study results show that digital libraries in madrasas are optimized for digital use, especially in education. In addition, the optimization strategy carried out is that the digital library has collections that are digitally recorded where the development of digital collections in the Madrasah includes analyzing user needs, mapping digital collection sources, and evaluating the use and IDs distributed to each library member including all students, teachers and education staff in the Madrasah. As well as optimizing the digital library in collaboration with the central library in Lamongan. The optimization of digital libraries can increase the popularity of digital libraries in madrasas and can expand library digital services.